Pengaruh Terapi Smile terhadap Tekanan Darah pada Pasien Hipertensi di RSUI Harapan Anda Kota Tegal - Elisa Artiyaningsih; Sri Wahyuni; Apriliyani Yulianti (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension, often referred to as high blood pressure, is a major global health problem that significantly increases the risk of atherosclerotic cardiovascular disease, heart failure, stroke, and kidney failure. Various complementary and alternative therapies have been explored to support conventional treatments in reducing blood pressure, one of which is smile therapy. This study aimed to analyze the effect of smile therapy on blood pressure among hypertensive patients at RSUI Harapan Anda Tegal. The research employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest method. A total of sixty hypertensive patients were selected through exhaustive sampling. Data were collected before and after the intervention and analyzed using the Wilcoxon test to determine the statistical significance of changes in blood pressure. The demographic characteristics of participants showed that most were in their early to mid-forties (36 individuals, 60%), predominantly female (38 individuals, 63.3%), with a junior high school education or below (25 individuals, 41.7%), and unemployed (41 individuals, 71.7%). The findings indicated that prior to the intervention, 41 participants (68.3%) had uncontrolled blood pressure. After undergoing smile therapy, 48 participants (80%) demonstrated improvement with more stable blood pressure levels. Statistical analysis revealed a significant effect of smile therapy on reducing blood pressure with a p-value of 0.000. These results suggest that smile therapy can serve as an effective, simple, and low-cost complementary intervention to help hypertensive patients manage their condition and improve overall health outcomes